IMPLEMENTASI KEBIJAKAN PENATAAN ORGANISASI PERANGKAT DAERAH DI KABUPATEN SOPPENG PROVINSI SULAWESI SELATAN - Rimba A. Sutra (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2016)
AbstractThis The purpose of this research is to get description about today structuring of localapparatus organization, focus of the problem in this study is “How organizational structuringof the regional district Soppeng?”. Based on these issues then this study aims to describethe implementation of the policy of the Organization of the District Planning Soppeng andunderstand how the implementation of the arrangement of the secretariat of the organizationof this region in terms of factors of communication, resources, Disposition and BureaucraticstructureResearch on Structuring the Organization of the District Soppeng a descriptive study withqualitative approach. The method used is the exploration of where the process of collectingdata and information from informants using an interview technique for primary data andresearch paper documents and literature for secondary data. As for the unit of analysis in thisstudy were those who considered gave the information needed by investigators, among others,offi cials of the District Government in the ranks Soppeng associated with the Technical TeamStructuring the Organization of the Region, namely the Regional Secretary, as well as someof the leadership of the agency, and from the district parliament Soppeng so that the resultingdata is descriptive and inductive data analysis of the data processing led to the rational modelof empirical research that is based on data and facts obtained directly in the fi eld.Keyword: Implementation Policy and Structuring the Organization